Survey on practice, perception and knowledge of doctors on antibiotic use and resistance in Penang Government Hospitals, Malaysia - Lim, Phin Phin; Teoh, Chee Jia; Chua, Cheah Chin; Tan, Sherene Su Ann; Ch’ng, Pao Pao; Liew, Ai Ch’i; Choong, Celine Yen Ching; Foong, Weng Siang; Lee, Yi Hui; Lim, Eu Joon; et al. (International Journal of Infection Control, 2020)
Inappropriate prescribing of antibiotics is one of the factors that lead to the development of antibiotic resistance. Therefore, understanding doctors’ practice, perception and knowledge is vital in targeting strategies to prevent antibiotic resistance. The aim of the study is to determine the practice, perception and knowledge of doctors on antibiotic use and resistance in Penang government hospitals. This is a cross sectional survey carried out in 6 Penang government hospitals from 9th January 2017 to 20th January 2017. A face-and-content validated questionnaire adapted from Abbo et al., was distributed to house officers (HO), medical officers (MO) and specialists/consultants (SC) and collected back within 5 working days. A total of 243 questionnaires were completed with a response rate of 60.45%. Majority of our respondents (91.6%) considered whether patient is critically ill and/or immunocompromised when selecting an antibiotic. Regardless of their position, doctors agreed that antibiotics are overused and antibiotic resistance is a significant problem nationally. However, MO tended to perceive antibiotic management programmes as an obstacle to good patient care. The mean knowledge score among respondents was 5.88 (1.92) out of 10. Adjusted analysis showed that SC have significantly higher mean knowledge score compared to HO and MO (p<0.001). Current antibiotic management programmes need to be continued to ensure judicious antibiotic use. However, a focused antimicrobial education strategy involving infectious diseases specialists, pharmacists and clinical microbiologists should be designed to improve the knowledge of HO and MO on antibiotic use and resistance, and to change their perception on antibiotic management programmes.